Ultralow thermal conductivity and improved ZT of CuInTe2 by high-entropy structure design. (May 2021) - Cai, Jianfeng; Yang, Junxuan; Liu, Guoqiang; Wang, Hongxiang; Shi, Fanfan; Tan, Xiaojian; Ge, Zhenhua; Jiang, Jun
Abstract: Entropy engineering has been widely applied to thermoelectrics as an effective strategy to reduce thermal conductivity. On the other hand，the increase of configuration entropy certainly decreases the electrical conductivity simultaneously, leading to the worsening of the thermoelectric performance. In this paper, we report a study on the high entropy structure design for chalcogenide CuInTe2 . Based on the analysis of electronic band structure, we show how to optimize the constituents of high-entropy compound to relieve the influence on electrical conductivity. Compared with (CuAg)0.5 (ZnGeGaIn)0.25 Te2, which has the highest configuration entropy among our samples, the optimized constituents of Cu0.8 Ag0.2 (ZnGe)0.1 (GaIn)0.4 Te2 shows the one order higher carrier mobility and little bit higher thermal conductivity. Finally, the highest ZT of 1.02 at 820 K is obtained in Cu0.8 Ag0.2 (ZnGe)0.1 (GaIn)0.4 Te2, accompanying with a very low thermal conductivity of 0.5 Wm −1 K −1 . This work provides a successful example of the high-entropy structure design for thermoelectrics, and it indicates that to reconcile the different requirements of thermal conductivity and electrical conductivity is crucial. Graphical abstract: Image 1 Highlights: The thermal conductivity of CuInTe2 is reduced by more than 80% by means of high-entropy structure design. The redesigned high-entropy compound, based on band structure analysis, increases the carrier mobility by one order of magnitude. The optimized high-entropy compound Cu0.8 Ag0.2 (ZnGe)0.1 (GaIn)0.4 Te2 achieves the maximum ZT of 1.02 at 820K.